Impact of Refractive Errors on the Academic Performance of High School Children of Lahore - Latif, Muhammad Zahid; Hussain, Intzar; Afzal, Saira; Naveed, Muhammad Asif; Nizami, Rahila; Shakil, Muhammad; Akhtar, Abdul Majeed; Hussain, Shabbir; Gilani, Syed Amir (Frontiers in Public Health, 2022)
Introduction The process of learning begins in childhood and accurate vision can greatly affects a child's learning capacity. It is documented that visual impairment in children can have a significant impact on their performance at school as well as their social interaction and development. Objective This research aimed to study the impact of refractive corrections on the academic performance of high school children in Lahore. Methodology A total of 2,000 students with equal distribution of gender, public, private school, and locality were included in the study. All students were screened for defective vision. The academic performance before and after corrections was recorded on the prescribed proforma. Results The prevalence of refractive error was high among the public high schools 244 (59.2%) as compared to the private schools 168 (40.8%). The area-based prevalence was higher among the students in urban settings 255 (62%) while in rural it was 157 (38%). It was found that in the public sector, the average score of academic results before the intervention was 56.39 ± 13.24 which was increased to 60.27 ± 14.94 after the intervention while in the private sector, before the intervention, the average score was 63.53 ± 17.50 which was improved to 67.12 ± 18.48. It was found to be statistically significant at p-value < 0.05. Conclusion A significant impact was observed in the average academic scores of the results after refractive corrections.